A REVIEW ABOUT HUMAN CYTOMEGALOVIRUS (HCMV) SEROPREVALENCE IN PREGNANT AND ABORTED WOMEN IN IRAQ (ARTICLE REVIEW) - Abdulla Kamil Abdulla (Scholar Express Journals, 2022)
The cytomegalovirus is the most prevalent member of the herpes virus family (CMV). Human cytomegalovirus (HCMV) is the most common cause of congenital malformation resulting from viral intrauterine infection in wealthy countries. In the majority of the world, CMV is endemic. The range of the HCMV sero-prevalence, which varies geographically, is between 30 and 100 percent. The presented review summarizes some studies conducted in Iraq to find out the Human cytomegalovirus (HCMV) seroprevalence in women who have had abortions and those who are pregnant.
Keywords: presented; countries; cytomegalovirus; common